Evaluation of photo-induced crosslinking of thymine polymers using FT-IR spectroscopy and chemometric analysis - Bortolato, Santiago Andres (2012)
The photo-induced immobilization of 4-vinylbenzyl thymine (VBT) and 4-vinylbenzyl triethyl ammonium chloride (VBA) copolymers has been investigated with the aid of grazing-angle specular-reﬂectance FT-IR spectroscopy. As irradiation time increases, changes in the structure of pendent thymine groups in the copolymer due to the crosslinking process result in shifts of the copolymer network’s vibrational frequencies, as well as changes in numerous IR band intensities. In this work, chemometric methods have been applied to the FT-IR data obtained while monitoring the time evolution of curing of VBT-VBA copolymers of varying composition. The spectral data obtained with FT-IR normally provide information only about the degree of conversion of the reactants in the ﬁnal product but there is no knowledge about how many compounds are involved or how they evolve over time. The use of the so-called Multivariate Curve Resolution-Alternating Least Squares allows the sequential estimation of the contribution to the signal due to the different species in the matrix data.